Goverment Control of Islamic Ideology Movement: A Case of Indonesia - Indra, Ristapawa; Ritonga, Mahyudin; Santosa, Fitrah (Journal of Al-Tamaddun, 2023)
Differences in views in the first precepts of the Pancasila version of the Jakarta Charter of 22 June 1945 became a genealogical factor that caused some Islamic groups to struggle relentlessly in realizing Islam as the basis of the philosophy and ideology of the state. Part of these groups' movements is compromise and radicalism. Therefore, this research aims to examine non-mainstream Islamic movements in the Indonesian political system. The phenomenological constructivism approach is used in understanding the views of the New Order and the Reform regimes in dealing with non-mainstream Islamic movements, through interview techniques and document analysis. These results showed that radical issues far exceed the normal level of Islamic movements in Indonesia. Furthermore, there is concern that certain groups oriented towards Islamic movements in Indonesia are more co-opted in the anti-Islamic global network sponsored by the United States and the West. The status of the New Order and Reform Regimes did not differ significantly in addressing various state issues related to the Islamic movement. For both regimes, non-mainstream Islamic movements should be strictly controlled. The most effective political instruments to control Islamic nationalist groups whose views differ from secular nationalist in terms of Pancasila as the state ideology are radical issues and terrorism.